Alternative dispute resolution in the Western Balkans : trends and challenges - Bungenberg, Marc; Koevski, Goran; Böhme, Bianca; Kocev, Ljuben; Fröhlich, Mareike; Zdraveva, Neda (Springer, 2024)
Alternative Dispute Resolution (ADR) is increasingly recognized as an attractive alternative to national court proceedings, especially in international business relations. This open access book focuses on ADR mechanisms in one specific geographical region: the Western Balkans. This region comprises Albania, Bosnia and Herzegovina, Croatia, North Macedonia, Montenegro, Kosovo, and Serbia. Although these countries generally have legal frameworks for ADR mechanisms in place, they remain largely underutilised in practice. Promoting ADR mechanisms in the countries of the Western Balkans could make them more attractive to foreign investors, thereby fostering economic growth. Additionally, the effective implementation of ADR mechanisms could have spill-over effects on national judiciaries, thereby increasing domestic rule of law standards. This would be highly beneficial for the Western Balkan countries, most of which are still aspiring to become Member States of the European Union (EU). To achieve this, they are required to promote the use of ADR mechanisms and align their legal frameworks with EU standards. Against this background, this book aims to explore the trends and challenges of ADR in the Western Balkans. The different chapters primarily focus on international commercial arbitration, investment treaty arbitration, and mediation. Some chapters address systemic challenges, such as capacity building and dispute prevention, which extend to the entire region. Others offer country-specific analyses of particular national framework. While some chapters adopt the perspective of international or EU law, others remain at the national level. Collectively, the wide diversity in topics and perspectives provides a comprehensive overview of the trends and challenges of ADR mechanisms in the Western Balkan.
Keywords: Dispute resolution (Law) -- Balkan Peninsula.; Règlement de conflits -- Balkans.